Pendampingan Kader Kesehatan dalam Pengelolaan Tabungan Sampah Anorganik dan Pelatihan Pembuatan Pupuk Kompos di Kabupaten Sukoharjo - Kusumawati, Yuli; Werdany, Kusuma Estu; Darnoto, Sri; Zulaekah, Siti; Sutrisna, Em; Wardiono, Kelik; Maimun, Muhammad Halim; Anis, Muchlison; Yuniar, Siska; Nurfauzia, Elita Nadia; Widananda, Clarisa; Rahmi, Anggraita Nur; Nurhaliza, Alfida Aulia Rahma Firdauzy; Fauziana, Eni; Pratiwi, Betty Intan (Warta LPM, 2023)
One of the problems in Tawang Village, Weru Subdistrict, Sukoharjo Regency is the accumulation of organic waste (leaves from the garden) and food waste, which can cause environmental pollution and transmit diseases, and also inorganic waste (used goods) that are abandoned, but can still be recycled.  This service activity aims to encourage the community to manage inorganic waste in the form of waste savings and process organic waste into compost. This activity is expected to motivate the community to protect the environment and improve the community's economy through waste utilization. The target of this activity is health cadres from Tawang Village for waste management education, making waste savings, and processing compost fertilizer. The method of activity in this community service is in the form of education and refresher information about waste, types of waste, and changing the mindset of the community that inorganic waste can still be collected, saved and sold and has economic value. Until organic can be composted. Educational media in waste management training uses power point media and animated videos. Waste management education activities by forming waste savings in health cadres in Tawang Village showed an increase in knowledge by 0.64 points with an average pre-test score of 11.64 points and an average post-test score of 12.28 points. There is an increase in the results of inorganic waste collection every month, waste savings are also increased.